The influence of growth and training loads on injury risk in competitive trampoline gymnasts - Patel, T. S.; McGregor, A.; Williams, K.; Cumming, S. P.; Williams, S. (Journal of Sports Sciences, 2021)
There is currently limited research exploring the relationship between growth, training load and injury in gymnasts. Twenty-one national level, trampoline gymnasts recorded training load and injury for 8-weeks. Percentage of predicted adult height (%PAH) was calculated using the Khamis-Roche method and used to define growth spurt status. Training load was calculated using the session rate of perceived exertion and analysed as differential loads and as a 7-day exponentially weighted moving average (EWMA7day). There was a significant non-linear association between %PAH and the probability of injury when adjusting for either training load metric (differential load, P = 0.015; EWMA7day; P = 0.008), with the highest injury risk estimated at ~90% PAH (circa growth spurt). The probability of injury significantly increased with increases in EWMA7day training load (RR: 1.88 95% CI: 1.21- 2.91, P = 0.005) but not with differential load. No significant interaction between %PAH, training load and the probability of injury were observed. Data suggest that competitive trampoline gymnasts are at an increased risk of injury during the adolescent growth spurt or with higher weekly training loads. Coaches should be educated and encouraged to identify periods of rapid growth and monitor training load, to reduce the risk of injury.